Assessment of runoff composition and residence time using stable isotopes and hydrochemical characteristics in Urumqi River Basin, northwest China - Siqi Wu; Fang Feng; Shuang Jin; Zhongqin Li; Michael A. Urban; Qiaohua Huang; Qiannian Shi (Journal of Hydrology: Regional Studies)
Study region: The Urumqi River, nourished by glaciers in arid regions of northwest China, plays a crucial role in the economic, ecological, and social development of the region. Study focus: Water resource management in arid regions is a perennial concern, compounded by the complex interplay of factors such as global warming and glacial response dynamics. Based on stable isotope and hydrochemistry data of 725 water samples, this study conducts a comprehensive analysis of the hydrochemical characteristics, runoff composition, and mean residence time of the Urumqi River Basin to enhance understanding of the hydrological processes of the river. New hydrological insights for the region: The hydrochemical type of river water is Calcium-Sulphate, with rock weathering as the main influence factor. Using the end-member mixing analysis (EMMA), it was calculated that the contribution ratios of ice and snow meltwater, atmospheric precipitation and groundwater to runoff were as follows: 3.81 %, 60.45 %, 35.75 % in spring; 28.99 %, 15.42 %, and 55.59 % in summer; and 22.72 %, 3.34 %, and 73.94 % in autumn. Based on the convolution integration method, the mean residence time (MRT) of water in the basin was calculated, and the result was 86 weeks (21.5months).